Treatment with retinoid X receptor agonist IRX4204 ameliorates experimental autoimmune encephalomyelitis - Chandraratna, Roshantha AS (Am J Transl Res, 2016)
Retinoid x receptors (RXRs) are master regulators that control cell growth, differentiation, and survival and form heterodimers with many other family members. Here we show that treatment with the RXR agonist IRX4204 enhances the differentiation of CD4(+) T cells into inducible regulatory T cells (iTreg) and suppresses the development of T helper (Th) 17 cells in vitro. Furthermore in a murine model of multiple sclerosis (experimental autoimmune encephalomyelitis (EAE)), treatment with IRX4204 profoundly attenuates both active and Th17-mediated passive disease. In the periphery, treatment with IRX4204 is associated with decreased numbers of CD4(+) T cells that produce pro-inflammatory cytokines. In addition, CD4(+) T cells express decreased levels of Ki-67 and increased expression of CTLA-4. Our findings demonstrate IRX4204 treatment during EAE results in immune modulation and profound attenuation of disease severity.